DIMENSI HAM DAN HUKUM ISLAM DALAM PUTUSAN MAHKAMAH KONSTITUSI NO. 46/PUU-VIII/2010 - Imam Mustofa (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This paper describes the dimensions of Human Right (HAM) enforcement in the Constitutional Court decision of number 46/PUU-VIII/2010. Two important things which are considered because law discourse development, especially the law of marriage in Indonesia resembling Constitutional Court's decision of number 46/PUU-VIII/2010 that affirmed protection of human rights of all citizens backgrounds without primordial. The result of the analysis is expected to create a comprehensive understanding of the human rights dimension of the Constitutional Court's decision of number 46/PUU-VIII/2010 and create an objective and comprehensive understanding that the decision was not contrary to the provisions of Islamic law.